2018
DOI: 10.1021/acs.energyfuels.8b03164
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Generation Potential of Oligocene Oil Shale Deposit at Onshore Penyu Basin, Chenor, Pahang, Malaysia

Abstract: This is the first study that focuses on the evaluation of a newly discovered oil shale deposit in the eastern Chenor area in the state of Pahang, Malaysia. Previously, this deposit was reported as carbonaceous/coaly mudstone. However, in this study, organic-rich immature carbonaceous mudstone containing above 15 wt % total organic carbon (TOC) is evaluated as oil shale, and that below 3.5 wt % TOC is termed mudstone. Oil shale and mudstone, which are significant sedimentary facies for oil and gas exploration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Meanwhile, the rock-eval pyrolysis technique has been widely applied in evaluating hydrocarbon generation potential [5][6][7], and related index (e.g., HI and OI) can be calculated by pyrolysis parameters to distinguish the types of kerogen. However, some studies indicated that the types of kerogen, which was obtained from HI and OI, may not always accurate [8][9][10]. Therefore, the TOC content, pyrolysis parameters, and other evaluation approaches can be utilized in combination to investigate hydrocarbon generation potential source rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the rock-eval pyrolysis technique has been widely applied in evaluating hydrocarbon generation potential [5][6][7], and related index (e.g., HI and OI) can be calculated by pyrolysis parameters to distinguish the types of kerogen. However, some studies indicated that the types of kerogen, which was obtained from HI and OI, may not always accurate [8][9][10]. Therefore, the TOC content, pyrolysis parameters, and other evaluation approaches can be utilized in combination to investigate hydrocarbon generation potential source rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Contribution to unconventional oil-shale resources. The properties of the organic-rich shale sediments and their contribution to petroleum-shale resources are generally assessed based on organic type and thermal ripening temperatures 20,21,28,41,44,45 . In this study, the integrated geochemical results and the kerogen microscopic features were discussed to characterize the organic facies and their potential as an oil-shale resource in the bituminous shale-bearing horizons of the Palana Formation in the Bikaner sub-basin of Rajasthan state.…”
Section: Discussionmentioning
confidence: 99%
“…Broadhead and Rinehart also declared that as the Mancos Shale becomes shallower it becomes thermally immature with very low oil generation potential. Makeen et al also obtained vitrinite reflectance and T max less than 0.5% and 429 °C, respectively, for an immature shale outcrop deposit in Malaysia with a considerably high TOC (>15 wt %).…”
Section: Comparison Based On Geochemical Characteristicsmentioning
confidence: 92%
“…Hence, in the absence of subsurface cores, proper outcrop sampling is very important. The candidate samples need to be collected from equivalent outcrops by digging trenches to minimize the potential influence of weathering. ,, Furthermore, as previously discussed, upon dissolution of carbonate and chlorite due to pyrite oxidation, the strength and density of shale formation decline and its porosity increases . Overall, they result in alteration of geomechanical properties of the rock.…”
Section: Comparison Based On Geomechanical Characteristicsmentioning
confidence: 99%